PERANCANGAN INTERIOR RESTORAN JUNG JAVA DI PESISIR PANTAI JEPARA - Ahmad Abdur Rois; Tri Prasetyo Utomo (Pendhapa, 2018)
ABSTRACTThe restaurantâ€™s interior design Jong Java will be designed with the theme â€œShip Jung Javaâ€ which takes the form of objects that were on board until the vessel Jung Java it self, and packed with style metaphor. The style can be identified by visual metaphor real and philosophically in the shape that gives an appropriate form of intact objects analogy. Making style is an embodiment of architectural styles to provide imagery on a building along with presented nuance ship Jung Java along with the history of the town of Jepara in an Interior Design Jung Java Restaurants in Coastal Jepara. Advantages in terms of facilities and style, â€œ Perancangan Interior Restoran Jung Java di Pesisir Pantai Jepara â€œ more interesting to be one of the culinary tourism in Jepara, as well as an effort to preserve one of the seafood dishes typical Jepara and Jepara maritime history.Keywords: Interior Design, Jung Java, Coastal Restaurant, Jepara